Development of osteogenic cell sheets for bone tissue engineering applications - Pirraco, Rogério (2011)
The use of scaffolds in combination with osteogenic cells has been the gold standard in bone tissue engineering strategies. These strategies have, however, in many cases failed to produce the desired results due to issues such as the immunogenicity of the biomaterials used and cell necrosis at the bulk of the scaffold related to deficient oxygen and nutrients diffusion. Here, we originally propose the use of cell sheet (CS) engineering as a possible way to overcome some of these obstacles. Osteogenic CSs were fabricated by culturing rat bone marrow stromal cells in thermoresponsive culture dishes. The CSs were recovered from the dishes using a low-temperature treatment and then were implanted subcutaneously in nude mice. New bone formation was verified from day 7 post-transplantation using X-ray, microcomputed tomography, and histological analysis. The presence of a vascularized marrow was also verified in the newly formed bone after 6 weeks of transplantation. Further, osteocytes were found in this newly formed tissue, supporting the conclusion that mature bone was formed after ectopically transplanting osteogenic CSs. These results therefore confirm the great potentiality of CS engineering to be used in bone tissue engineering applications